2009
DOI: 10.1016/j.aquatox.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acid mine drainage on the genetic diversity and structure of a natural population of Daphnia longispina

Abstract: a b s t r a c tThe increase in resistance to contaminants can result in the loss of genetic diversity of impacted populations. In this work, the effects of acid mine drainage (AMD) on the genetic diversity and structure of a historically exposed population of Daphnia longispina were evaluated using amplified fragment length polymorphism (AFLP) analysis. Individual sensitivity to acute copper exposure was determined in order to characterize the populations in terms of metal tolerance and in an attempt to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…Fundamental researches into Daphnia's molecular phylogenesis in different geographical areas, such as Europe (Schwenk et al, 2000), North America (Colbourne & Hebert, 1996), South America (Adamowicz et al, 2004), and Australia (Colbourne et al, 2006) are of particular interest. Daphnia has been used in a series of population genetics studies (Schwenk et al, 1998;Hellsten & Sundberg, 2000;Atienzar & Jha, 2004;Mergeay et al, 2005;Picado et al, 2007;Martins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental researches into Daphnia's molecular phylogenesis in different geographical areas, such as Europe (Schwenk et al, 2000), North America (Colbourne & Hebert, 1996), South America (Adamowicz et al, 2004), and Australia (Colbourne et al, 2006) are of particular interest. Daphnia has been used in a series of population genetics studies (Schwenk et al, 1998;Hellsten & Sundberg, 2000;Atienzar & Jha, 2004;Mergeay et al, 2005;Picado et al, 2007;Martins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hereafter, increasing fitness costs will be defined in terms of reduced reproductive output, growth rates and population growth and physiological costs in terms of increasing energy demand according to Shirley and Sibly (1999). Previous studies have reported that long term adaptation to acid main drainage did not affect genetic diversity of neutral markers in these D. longispina populations (Martins et al 2007;Martins et al 2009). In a quantitative genetic study testing up to 40 different clones for resistance to copper and zinc, Agra et al (2010) found only high degrees of resistance to copper in D. longispina clones from populations affected by S. Domingos acid drainage.…”
Section: Introductionmentioning
confidence: 99%
“…At this regard, it is worth mentioning that similar studies, based on AFLP, which succeeded in finding effects induced by contaminant on population genetics, usually referred to more toxic substances than the molecules considered in this study (Bach and Dahllof, 2012;Gardestrom et al, 2008;Martins et al, 2009;Andre et al 2010). Indeed, an in vivo assay aimed at investigating the evolutionary toxicology of perfluoralkyl substances (PFOS, PFOA, PFBS) in a multigeneration toxicity test on Chironomus riparius was recently carried out (Stefani et al, 2014).…”
Section: Discussionmentioning
confidence: 93%